Importância dos testes sorológicos para o diagnóstico de paracoccidioidomicose por paracoccidioides lutzii - Angelo, Patricia Del [UNIFESP] (2018)
Paracoccidioidomycosis (PCM) is an endemic systemic mycosis, caused by the thermodymorphic fungus Paracoccidioides spp., being of great interest to the countries of Latin America, mainly to Brazil. Two different species have been identified: Paracoccidioides brasiliensis (with three cryptic species S1, PS2 and PS3) and Paracoccidioides lutzii. It presents at 25ºC in filamentous phase and at 37ºC in yeast phase, its dimorphism seems to be directly linked to the virulence. PCM is a fungal infection that can lead the individual to various sequelae and even death. For this reason it is very important the diagnosis to initiate the appropriate therapy cure of the patient. Serological tests are essential indirect methods used in the diagnosis and prognosis of the disease, in which specific antigens and antibodies are screened in the patient's serum. In order to increase the specificity and sensitivity of the serological tests it is advisable to use two or more serological tests for a definitive diagnosis. Among the techniques used, doubleagarose gel (ID), easy to handle and run immunodiffusion and conventional enzyme immunoassay (ELISA) are the most commonly used in routine diagnostic laboratories. In this investigation we intend to show the importance of the serological tests for the diagnosis of PCM, through two different methodologies, Immunodiffusion and Elisa with the intention of verifying the feasibility of the techniques used for the detection of antiP antibodies. lutzii in the sera of PCM patients by P. lutzii using complex antigenic preparations.